Social introduction to library services for international students: The international student reception at Kent State University Libraries. Issue 3 (3rd April 2017) - Sheu, Feng-Ru; Panchyshyn, Roman S.
Abstract : Purpose: The purpose of this paper is to explore the effectiveness that a social function, an international student reception, has on making international students comfortable with library services and resources in an American academic library at Kent State University. Design/methodology/approach: A structured questionnaire was used to collect responses from attendees of an international student reception. The questionnaire was distributed both in-person and by e-mail. Ninety-three valid responses were received. The descriptive survey method was used in the study. Findings: The findings reveal that the reception is attracting its target market, international students who have been enrolled at the university for less than one year. Food selection is critical to the success of the reception. However, there is room for improvement in many areas, such as the timing of the event, physical location and interactions between library staff and the international students. Research limitations/implications: The survey was limited to only the international students who could attend the reception. Practical implications: The study shows that partnership between the library and another department on campus (Office of Global Education) was a major key in the success of these receptions. Also, findings support that the comfort level of the students is a critical factor for the introduction of library services to international students. Future research is needed to measure the long-term impact of social event on library use. Originality/value: This is the first case study in the literature where an academic library evaluates the impact of a social function, a reception, to gauge its ability to make international students comfortable with the library and its services.